2012
DOI: 10.4103/0975-7406.94116
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and characterization of Cefuroxime Axetil nanoemulsion for improved bioavailability

Abstract: Cefuroxime Axetil nanoemulsion was formulated to address the problem of poor oral bioavailability. Formulation was manufactured utilizing Capmul MCM, Soya lecithin, Deoxycholic acid, Pluronic F127 and distilled water. Mean globular size of 121.3 nm was obtained. Drug content of nanoemulsion was found to be 97.12±0.27%w/v. 80.7261% of the drug was diffused from nanoemulsion, as compared with 51.0048% diffused from the plain Cefuroxime axetil suspension. In vivo studies indicated AUC0-24: 325.3 for nanoemulsion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Recently, micro/nano drug formulations have been produced via combination of micro/nanotechnology and pharmaceutical sciences, which is a most promising strategy for improving the bioavailability of water-insoluble drugs because the high surface area of micro/nano drugs can effectively enhance drug solubility and stability [ 26 ]. In addition, many studies showed that the low crystallinity of micro/nano drugs played a significant role in enhancing the dissolution rate [ 27 , 28 ]. However, the conventional methods for preparing micro/nano drugs, such as spray drying, liquid antisolvent precipitation, emulsion-solvent evaporation, and wet media milling are not suitable for many pharmaceutical compounds [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, micro/nano drug formulations have been produced via combination of micro/nanotechnology and pharmaceutical sciences, which is a most promising strategy for improving the bioavailability of water-insoluble drugs because the high surface area of micro/nano drugs can effectively enhance drug solubility and stability [ 26 ]. In addition, many studies showed that the low crystallinity of micro/nano drugs played a significant role in enhancing the dissolution rate [ 27 , 28 ]. However, the conventional methods for preparing micro/nano drugs, such as spray drying, liquid antisolvent precipitation, emulsion-solvent evaporation, and wet media milling are not suitable for many pharmaceutical compounds [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%